Rational Emotional Behavior Therapy (REBT) to Reduce Anxiety Bullying Victims in Adolescents (Journal of Family Sciences, 2020)
Bullying is an act of hurting others physically and mentally and is done repeatedly. The case of bullying is one of the issues that are still a particular concern at Muhammadiyah Boarding School Al Mujahidin Gunungkidul. This study aims to reduce the anxiety of victims of bullying by using a rational emotive behavior therapy (REBT) counseling approach. The subjects of this study were students of class VII Muhammadiyah Boarding School Al Mujahidin Gunungkidul, who were victims of bullying in classes and schools with a total of 28 students. This research was conducted from August 1 to September 30, 2017. The type and design of the study used collaborative action research. Data analysis was carried out quantitatively using a questionnaire for victims of bullying anxiety. Qualitative analysis is performed on data obtained from interviews, observations, and follow-up. The counseling program with the rational emotive behavior therapy (REBT) approach has proven to be effective and has an effect on reducing anxiety in bullying victims, which is characterized by a decrease in anxiety scores. In addition, the subject feels that he is not alone or not isolated; self-confidence increases have a role towards others and can observe and follow instructions given by the researcher.